EFISIENSI RANTAI NILAI BIJI KAKAO DI KABUPATEN BIREUEN - Yusdiana Yusdiana; Hilda Pratiwi; Cut Millatin Amalia (Universitas Teuku Umar, 2021)
The role of cocoa in regional-growth and agro-industry development. The development of cocoa agribusiness is a national dilemma that has been becoming a concern for the farming sector. Cocoa development is not only creating livelihood, but also increasing farmers' income and opening up opportunities to get value added of products. This study aims to determine the efficiency of the cocoa bean value chain in Bireuen Regency by analyzing marketing channels, trading margins and determining the main stages of cocoa business activities where value chain actors can increase product value, producing an efficient value chain map, in order to increase farmers' income and develop cocoa farming commodity in Bireuen Regency. This study uses a qualitative method while this method is considered relevant to explore data and information. The data used are primary data obtained from direct interviews with respondents from several parties involved in the cocoa bean value chain. Data analysis was carried out descriptively, namely collecting, processing, presenting, and analyzing quantitative data. The method used to analyze the value chain of cocoa beans is economic value added, namely the analysis to determine the economic value added of an EVA = (Net Income) / (Total Cost) x 100%. The EVA value is 87.5%, meaning that every harvest period cocoa farmers can get a net profit of 87.5% of the total costs incurred.